3T vs. 7T fMRI: capturing early human memory consolidation after motor task utilizing the observed higher functional specificity of 7T - Kreitz, Silke; Mennecke, Angelika; Konerth, Laura; Rösch, Julie; Nagel, Armin Michael; Laun, Frederik Bernd; Uder, Michael; Dörfler, Arnd; Heß, Andreas (Frontiers in Neuroscience, 2023)
Functional magnetic resonance imaging (fMRI) visualizes brain structures at increasingly higher resolution and better signal-to-noise ratio (SNR) as field strength increases. Yet, mapping the blood oxygen level dependent (BOLD) response to distinct neuronal processes continues to be challenging. Here, we investigated the characteristics of 7 T-fMRI compared to 3 T-fMRI in the human brain beyond the effect of increased SNR and verified the benefits of 7 T-fMRI in the detection of tiny, highly specific modulations of functional connectivity in the resting state following a motor task.<br